Educating Bela Negara Values Using Puppet Media to Al-Azhar Kelapa Gading Surabaya Kindergarten - Mahimma Romadhona; Aileena Solicitor Costa Rica El Chidtian; Rosiana Febrianita (Nusantara Science and Technology Proceedings, 2022)
Learning and inculcating character that contains the values of Bela Negara need to be carried out from an early age, starting from the age of 5 years or pre-school age. Character education for early childhood is intended to instill good values so that they can become good habits when children become adults or at the next level of education. The problems faced today are the children's lack of knowledge about the values of Bela Negara and their lack of knowledge about wayang art. Therefore, we need an extension of the values of Bela Negara to kindergarten children in a simple, interesting, and attractive way, namely through storytelling using wayang media. The purpose of this community service activity is to increase children's insight and knowledge about the values of defending the country and to introduce the art of wayang to children. The design of the wayang characters used is called Panca Satria, namely 5 little heroes with national defense characters, which are the results of the basic research of researchers. This outreach activity was carried out at Al-Azhar Kelapa Gading Surabaya Kindergarten, which is located at Taman Bhaskara No. 1, Mulyorejo, Surabaya. With this community service activity, it is hoped that early childhood, especially kindergarten children, can recognize the value of Bela Negara from an early age as a form of love for the Indonesian homeland.